Competency Recommendations for Advancing Nursing Informatics in the Next Decade: International Survey Results - Charlene Ronquillo; Maxim Topaz; Lisiane Pruinelli; Laura-Maria Peltonen; Raji Nibber (Ios Press, 2025)
The IMIA-NIstudents’ and emerging professionals’ working group conducted a large international survey in 2015 regarding research trends in nursing informatics. The survey was translated into half-a-dozen languages and distributed through 18 international research collaborators’ professional connections. The survey focused on the perspectives of nurse informaticians. A total of 272 participants responded to an open ended question concerning recommendations to advance nursing informatics. Five key areas for action were identified through our thematic content analysis: education, research, practice, visibility and collaboration. This chapter discusses these results with implications for nursing competency development. We propose how components of various competency lists might support the key areas for action. We also identify room to further develop existing competency guidelines to support in-service education for practicing nurses, promote nursing informatics visibility, or improve and facilitate collaboration and integration with other professions.
Forecasting Informatics Competencies for Nurses in the Future of Connected Health